2016
DOI: 10.1007/s00442-016-3712-4
|View full text |Cite
|
Sign up to set email alerts
|

Foliar uptake of fog in coastal California shrub species

Abstract: Understanding plant water uptake is important in ecosystems that experience periodic drought. In many Mediterranean-type climates like coastal California, plants are subject to significant drought and wildfire disturbance. During the dry summer months, coastal shrub species are often exposed to leaf wetting from overnight fog events. This study sought to determine whether foliar uptake of fog occurs in shrub species and how this uptake affects physiology and fuel condition. In a controlled greenhouse experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Resistances provide illustrative examples, but all these can vary significantly based on leaf anatomy and water gradients within the leaf. Example images of surface properties are taken from Burgess and Dawson (; endophyte), Martin and Von Willert (; hydathode), Goldsmith (unpublished; cuticle), and Emery (; stomata and trichome) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Pathways Of Water Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistances provide illustrative examples, but all these can vary significantly based on leaf anatomy and water gradients within the leaf. Example images of surface properties are taken from Burgess and Dawson (; endophyte), Martin and Von Willert (; hydathode), Goldsmith (unpublished; cuticle), and Emery (; stomata and trichome) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Pathways Of Water Movementmentioning
confidence: 99%
“…Recent work has called for a shift in this thinking to consider plant water movement in both directions (Goldsmith, 2013). Yet some studies have observed species that do not carry out FWU co-occurring with species that do carry out FWU (Emery, 2016;Limm, Simonin, Bothman, & Dawson, 2009). Emery (2016) suggested that stomatal crypts resulted in limited FWU, however, there remains no clear explanation for species-level variation in FWU.…”
Section: Physical and Biological Requirements Of Fwumentioning
confidence: 99%
“…Although fog water uptake was not detected in four of the 456 shrub species sampled, this does not mean conclusively that these species cannot take up fog. Adenostoma 457 fasciculatum, Artemisia californica, and Salvia leucophylla can take up fog water through their leaves in 458 controlled settings (Emery 2016). The time elapsed between sampling dates (two weeks to one month), 459 may have prevented detection of fog in the stem tissue of some species.…”
Section: Fog Patterns and Fog Water Uptake 435 436mentioning
confidence: 99%
“…Despite the lack of isotopic evidence of fog water in plant 489 tissue, new leaf growth has been observed in A. californica following late summer fog events and prior to 490 the first fall rain events (Emery, personal observations). Although B. pilularis can take up fog water 491 through leaves (Emery 2016), root uptake is also possible if fog deposition is heavy. At two of the field 492 sites, B. piluaris was using non-trivial proportions of fog water ( Figure 5B-C flammability (Anderson 1970, Martin et al 1994.…”
Section: Cc-by-nc-ndmentioning
confidence: 99%
“…, Baguskas et al. , Emery ), enhance carbon assimilation (Berry and Smith , Gotsch et al. ), and increase hydraulic function (Laur and Hacke ).…”
Section: Introductionmentioning
confidence: 99%